1981
DOI: 10.1042/bj1970315
|View full text |Cite
|
Sign up to set email alerts
|

Specificity of mammalian spermidine synthase and spermine synthase

Abstract: 1. The specificity of rat prostatic spermidine synthase and spermine synthase with respect to the amine acceptor of the propylamine group was studied. 2. Spermidine synthase could use cadaverine (1,5-diaminopentane) instead of putrescine, but the Km for cadaverine was much greater and the rate with 1mM-cadaverine was only 10% of that with putrescine. 1,3-Diaminopropane was even less active (2% of the rate with putrescine) and no other compound tested (including longer alpha,omega-diamines, spermidine and its h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
19
0

Year Published

1983
1983
2016
2016

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 59 publications
(24 citation statements)
references
References 33 publications
5
19
0
Order By: Relevance
“…The mammalian systems that have been investigated, however, show that active OmDCase decreases in response to additions of putrescine (27) and the putrescine analog, 1,3-diaminopropane (28,29). Because 1,3-diaminopropane is not readily metabolized to the corresponding spermidine analog (30), the data suggest that putrescine has a negative effect independent of its conversion to spermidine. Both OrnDCase antizyme formation (20) and loss of OrnDCase protein (31) have been reported in cells treated with 1,3-diaminopropane.…”
Section: Discussionmentioning
confidence: 90%
“…The mammalian systems that have been investigated, however, show that active OmDCase decreases in response to additions of putrescine (27) and the putrescine analog, 1,3-diaminopropane (28,29). Because 1,3-diaminopropane is not readily metabolized to the corresponding spermidine analog (30), the data suggest that putrescine has a negative effect independent of its conversion to spermidine. Both OrnDCase antizyme formation (20) and loss of OrnDCase protein (31) have been reported in cells treated with 1,3-diaminopropane.…”
Section: Discussionmentioning
confidence: 90%
“…The specificity of the enzyme is significantly different when compared to that of propylamine transferases from eubacteria [12] and eukaryotes [45]; indeed the enzyme from S . solfataricus is able to transfer the propylamine group from decarboxy-AdoMet to a primary amino group linked to a trimethylenic as well as to a tetramethylenic chain.…”
Section: Discussionmentioning
confidence: 99%
“…1) was formed (71), and it was later shown that aminopropylcadaverine is as effective as Spd in restoring normal growth to a polyamine auxotroph (72). Production of aminopropylcadaverine by the AdoMetDC/SpdSyn pathway has also been demonstrated with mammalian and fungal cells (73,74).…”
Section: Polyamines In Bacteriamentioning
confidence: 99%